IL-17 induces antitumor immunity by promoting beneficial neutrophil recruitment and activation in esophageal squamous cell carcinoma. (2nd January 2018) - Chen, Chang-Long; Wang, Ying; Huang, Chun-Yu; Zhou, Zi-Qi; Zhao, Jing-Jing; Zhang, Xiao-Fei; Pan, Qiu-Zhong; Wu, Jiang-Xue; Weng, De-Sheng; Tang, Yan; Zhu, Qian; Yuan, Lu-Ping; et al.
ABSTRACT: Interleukin (IL)-17 has been reported to play a controversial role in tumor immunity. Our previous studies showed that infiltration of IL-17-producing cells in esophageal squamous cell carcinoma (ESCC) induced tumor protective immunity by recruiting CD8+T lymphocytes, natural killer (NK) cells, and B lymphocytes into the tumor microenvironment. However, the mechanism of IL-17 regulation of tumor-associated neutrophils remains elusive in ESCC. In this study, we therefore evaluated the accumulation of myeloperoxidase (MPO)+ neutrophils and its association with IL-17-producing cells within ESCC tumor nests. We also investigated the effects of IL-17 on the recruitment and antitumor activity of neutrophils. MPO+ neutrophil infiltration was found to predict a favorable prognosis in ESCC patients and was positively correlated with IL-17+ cell density. IL-17 stimulated ESCC tumor cells to release more of the CXC chemokines CXCL2 and CXCL3, which are involved in neutrophil migration. Furthermore, IL-17 potentiates the direct killing capability of neutrophils by enhancing the production of cytotoxic molecules, including reactive oxygen species (ROS), MPO, TNF-related apoptosis-inducing ligand (TRAIL), and IFN-γ. Experiments in mice suggested that IL-17 alone might not affect tumor progression in the tumor-bearing host, but IL-17 can inhibit tumor growth by promoting beneficial neutrophil infiltration and activation at tumor sites. As emerging evidence indicates that targeting tumor-associated neutrophils is a strategy for antitumor therapy, our findings reveal a positive contribution of IL-17 to the modulation of neutrophil-mediated antitumor immunity in ESCC. This study provides further understanding of the mechanisms that selectively regulate functional activities of neutrophils, which may be critical for developing new tumor immunotherapy.